2022
DOI: 10.1186/s13071-022-05405-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals dynamic expression of lncRNAs and mRNAs in caprine endometrial epithelial cells induced by Neospora caninum infection

Abstract: Background The effective transmission mode of Neospora caninum, with infection leading to reproductive failure in ruminants, is vertical transmission. The uterus is an important reproductive organ that forms the maternal–fetal interface. Neospora caninum can successfully invade and proliferate in the uterus, but the molecular mechanisms underlying epithelial-pathogen interactions remain unclear. Accumulating evidence suggests that host long noncoding RNAs (lncRNAs) play important roles in cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…For example, a total of 81, 126, 82 and 131 miRNAs were differentially expressed (DE) in porcine alveolar macrophages [ 27 ], pig splenocytes [ 28 ], livers of domestic cats [ 29 ], and mouse spleen [ 30 ], respectively, during infections with Toxoplasma gondii , an obligate intracellular zoonotic protozoan parasite similar to N. caninum in its morphological and biological features but differing in its life cycle and biological effects on host cells [ 31 33 ]. Previously, our group found that N. caninum infection significantly altered the expression patterns of host cell long ncRNAs, which are some of the most important regulatory ncRNAs [ 34 ]. In the present study, we investigated dynamic miRNA profiles in caprine endometrial epithelial cells (EECs) during their infections with N. caninum .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a total of 81, 126, 82 and 131 miRNAs were differentially expressed (DE) in porcine alveolar macrophages [ 27 ], pig splenocytes [ 28 ], livers of domestic cats [ 29 ], and mouse spleen [ 30 ], respectively, during infections with Toxoplasma gondii , an obligate intracellular zoonotic protozoan parasite similar to N. caninum in its morphological and biological features but differing in its life cycle and biological effects on host cells [ 31 33 ]. Previously, our group found that N. caninum infection significantly altered the expression patterns of host cell long ncRNAs, which are some of the most important regulatory ncRNAs [ 34 ]. In the present study, we investigated dynamic miRNA profiles in caprine endometrial epithelial cells (EECs) during their infections with N. caninum .…”
Section: Introductionmentioning
confidence: 99%